2015
DOI: 10.1371/journal.pone.0123742
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Metal Profiles with Altered Glucose Levels and Diabetes Risk: A Population-Based Study in China

Abstract: BackgroundElevated heavy metals and fasting plasma glucose (FPG) levels were both associated with increased risk of cardiovascular diseases. However, studies on the associations of heavy metals and essential elements with altered FPG and diabetes risk were limited or conflicting. The objective of this study was to evaluate the potential associations of heavy metals and essential trace elements with FPG and diabetes risk among general Chinese population.MethodsWe conducted a cross-sectional study to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 66 publications
1
73
0
2
Order By: Relevance
“…In addition, urinary zinc, molybdenum and tungsten levels were associated with increased risk of diabetes in a dose-dependent manner. Low prevalence of diabetes (9.7%) and of impaired fasting glucose (11.6%) in this Chinese sample population (Feng et al 2015) means that sample size of 2,242 would not be likely to provide sufficient power to demonstrate Cd exposure effects.…”
Section: Cadmium and Diabetic Riskmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, urinary zinc, molybdenum and tungsten levels were associated with increased risk of diabetes in a dose-dependent manner. Low prevalence of diabetes (9.7%) and of impaired fasting glucose (11.6%) in this Chinese sample population (Feng et al 2015) means that sample size of 2,242 would not be likely to provide sufficient power to demonstrate Cd exposure effects.…”
Section: Cadmium and Diabetic Riskmentioning
confidence: 91%
“…Comparing the above three groups, increased susceptibility to kidney Cd toxicity (demonstrated by albuminuria) was seen in a diabetic group . In a study of 2,242 adults (75.1% non-smokers, mean age 53 yrs) in Wuhan, China, Feng et al (2015) found urinary Pb levels were associated with impaired fasting blood glucose levels, but urinary Cd levels were not associated with diabetic risk or impaired fasting blood glucose levels. In addition, urinary zinc, molybdenum and tungsten levels were associated with increased risk of diabetes in a dose-dependent manner.…”
Section: Cadmium and Diabetic Riskmentioning
confidence: 98%
“…The concentrations of TEs including Cu, Zn, Se, Mo, and As in fresh and spent dialysate samples as well as urine samples were measured by an inductively coupled plasma mass spectrometry with an octopole-based collision/reaction cell (Agilent 7700 Series, Waldbronn, Germany) following the method reported by Feng et al [31]. Accuracy and precision of the results were guaranteed by the analysis of standard reference materials (SRMs) 2670a and 1640a.…”
Section: Methodsmentioning
confidence: 99%
“…Ecological toxicants like heavy metals, bisphenol A, polychlorinated biphenyls, pesticides, etc. have been allied with several metabolic disorders and liver diseases . Chen et al .…”
Section: Discussionmentioning
confidence: 99%